2005
DOI: 10.1128/jvi.79.2.823-833.2005
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Vif Protein Shows Less Restriction of Human Immunodeficiency Virus Type 2 by APOBEC3G

Abstract: Viral infectivity factor (Vif) is one of the human immunodeficiency virus (HIV) accessory proteins and is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 56 publications
2
22
0
Order By: Relevance
“…Therefore, it appears that HIV-2 Vif is functionally similar to HIV-1 Vif. Surprisingly, however, it has also been reported that an HIV-2 proviral clone lacking a functional vif gene can replicate effectively in a human T-cell line, termed H9, that expresses hA3G mRNA and that is nonpermissive for Vif-deficient HIV-1 (44). In contrast, primary CD4…”
Section: Other Exogenous Viruses and The Apobec3 Proteinsmentioning
confidence: 95%
“…Therefore, it appears that HIV-2 Vif is functionally similar to HIV-1 Vif. Surprisingly, however, it has also been reported that an HIV-2 proviral clone lacking a functional vif gene can replicate effectively in a human T-cell line, termed H9, that expresses hA3G mRNA and that is nonpermissive for Vif-deficient HIV-1 (44). In contrast, primary CD4…”
Section: Other Exogenous Viruses and The Apobec3 Proteinsmentioning
confidence: 95%
“…The antiretroviral activity of APOBEC3-subfamily proteins extends well beyond HIV-1 and has been shown to inhibit various lentiviruses such as HIV-2, SIVmac, SIVagm, and EIAV [114,122,128,129]. There is also evidence that some APOBEC proteins can target a variety of retroviral substrates, such as various oncoviruses and spumaviruses.…”
Section: Apobec3mentioning
confidence: 96%
“…One such factor is APOBEC3G, which was shown to antagonize the activity of HIV-1 Vif; its expression was postulated to underlie the difference among some target cells lines in their susceptibility to Vif-negative HIV-1 (29). Curiously, although HIV-2 Vif can complement Vif-negative HIV-1 (30), it is poorly antagonized by APOBEC3G, and cell lines expressing APOBEC3G can be susceptible to Vif-negative HIV-2 but not to Vif-negative HIV-1 (31). Different species-specific host restriction factors have been proposed to interact with the CypA-binding domain of CA during early phases of HIV-1 infection of certain nonpermissive simian cells (21,32,33).…”
Section: Discussionmentioning
confidence: 99%